Increased mineral fertilizer use on maize can improve both household food security and regional food production in East Africa. (February 2023) - Falconnier, Gatien N.; Leroux, Louise; Beillouin, Damien; Corbeels, Marc; Hijmans, Robert J.; Bonilla-Cedrez, Camila; van Wijk, Mark; Descheemaeker, Katrien; Zingore, Shamie; Affholder, François; Lopez-Ridaura, Santiago; Malézieux, Eric; et al.
Abstract: CONTEXT: Despite recent improvements in living standards, a substantial proportion of farm households in sub-Saharan Africa (SSA) is food insecure, and increasing crop productivity could help address this problem. OBJECTIVE: We estimated the effect of increasing maize yields with mineral fertilizer on household food security and on regional and national maize supply in two East African countries - Uganda and Tanzania. METHODS: We estimated maize yield response to nitrogen (N) fertilization with a machine learning model trained on 15, 952 observations of maize responses to fertilizer across SSA. Together with spatial price data, we used this model to quantify the profit-maximizing N fertilizer input for a nationally-representative sample of 4188 agricultural households in the two countries. We computed a food availability indicator for all households. RESULTS AND CONCLUSIONS: The mean profit-maximizing N input was 82 kg/ha in Tanzania, but it was much lower in Uganda (24 kg/ha) mostly because of less favorable prices. The profit-maximizing N input was above the reported N input for 95% of the households in Tanzania and for 43% of the households in Uganda. It was predicted to increase the food availability ratio of food insecure maize growers by 95% in Tanzania, and by 25% in Uganda. The administrative regions where maize supply could increase most were not the same as the regions where the increase in household-level food security was largest. With increased fertilization, food insecure maize growing households (35% in Tanzania and 42% in Uganda) could only contribute about 20% of the overall increase in maize supply, whereas the 20 to 30% food secure households that have a larger area planted with maize could contribute >60%. SIGNIFICANCE: Our study makes two key contributions: i) a substantial increase in national maize supply is more likely to come from already food secure households with relatively large farms, while food insecure households with small farms may nevertheless increase their household-level food security through maize intensification, and ii) high potential areas to increase maize domestic production do not necessarily match with areas where there is immediate scope to improve household-level food security. Graphical abstract: Unlabelled Image Highlights: Food security analysis with current and profit-maximizing N input in East Africa Food secure households are main contributors of national increase in grain supply Food insecure households also benefit for their food security Variations in maize and fertilizer price impact strongly opportunities to reduce food insecurity